Rivers as Catalysts for Environmental Mobilization: a Test in the Eastern Lombard Plain - Osti, Giorgio (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
The paper concerns a case of environmental mobilisation in the Chiese basin, a medium-length river that flows between Trentino and Lombardy. The case seems to contradict the idea that ecological mobilisation is almost absent in semi-rural areas due to cultural and territorial factors. To verify this hypothesis, the socio-environmental mobilisation along the Chiese is compared with that of the neighbouring river basins. We found more long-term and inclusive mobilisation along the Chiese river, and this is due not only to the local identity strength of the river, but also the occurrence of catalytic events that have threatened the sense of dignity and territorial justice of the inhabitants of the Chiese valley. After reviewing the specific literature on environmental mobilisation, we adopted a model of ‘baseline conditions-events catalysts-collective action’ and applied it to the specific case. The history of the mobilisation serves as empirical material on which to test the hypothesis.